(untitled) (Universal International Scientific Journal, 2026)
This article provides an in-depth analysis of the process of women’s adaptation to a new social environment based on psychological, pedagogical, social and cultural factors. The mechanisms of women’s adaptation to the family, work community, new place of residence, migration processes, professional environment, digital space and intercultural environment, their supporting systems and pedagogical strategies that facilitate adaptation are examined. The study further explains the impact of women’s psychological resources, the institution of the family, state policy and social infrastructure on adaptation based on scientific evidence.